2000
DOI: 10.1088/0953-2048/13/6/305
|View full text |Cite
|
Sign up to set email alerts
|

Melt processing and characterization of bulk NdBaCuO

Abstract: Nd 1+x Ba 2−x Cu 3 O 7−δ (Nd123) bulk superconductors have been synthesized under air and by the oxygen-controlled melt growth method (OCMG). We have studied the effects of Nd 4 Ba 2 Cu 2 O 10 (Nd422) additions, processing rates and doping effects on the microstructure and the superconducting properties in the OCMG-processed samples. Unlike the YBCO system, platinum doping or Nd422 additions do not refine the Nd422 secondary phase inclusions. On the other hand, Ce doping is effective in Nd422 refinement as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The particle size of Nd422 embedded in the matrix is much larger than Gd211. One possible explanation is that the platinum doping does not refine the Nd422 particles during the growth [24].…”
Section: Superconducting Properties and Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…The particle size of Nd422 embedded in the matrix is much larger than Gd211. One possible explanation is that the platinum doping does not refine the Nd422 particles during the growth [24].…”
Section: Superconducting Properties and Microstructurementioning
confidence: 99%
“…The melting point of MgO is sufficiently high; there is no T max limit for this method. The cold-seeding growth of Nd-Ba-Cu-O single grains, which is largely limited by the high T p [12][13][14][15], is realized by the present method.…”
Section: Introductionmentioning
confidence: 98%
“…Kojo et al [7] investigated the magnetic field dependence of J c for the oxygen-controlled melt-growth (OCMG)-processed Nd-system bulks with a different volume fraction of the Nd 4 Ba 2 Cu 2 O 10 (Nd-422) phase. Monot-Laffez et al [8] reported on the effects of Nd-422 addition, platinum and Ce doping on the microstructure and the superconducting properties in the OCMG-processed samples. A detailed study of grain growth in a Nd-system superconductor was performed and a schematic phase diagram was constructed in the peritectic solidification region at various temperatures [9].…”
Section: Introductionmentioning
confidence: 99%